Measuring the Effect of Parents’ Socio-economic Status and Early Literacy Experience on Moroccan Students’ Reading Comprehension Development: An Illustration from PIRLS 2016 - Nadori, Neirouz (Yayasan Visi Intan Permata, 2019)
Because students? reading development is a subject to many influences, home-based factors constitute important components in this process. Parents socio-economic status (parents? occupation and educational level) as well as early literacy experience before school are strongly linked to students? reading comprehension achievement. However, less is known about home-based effects on Moroccan students? reading comprehension development. This research is concerned with investigating the relations between early literacy experience before school, parents? occupation and educational level and reading comprehension development. This study is framed within developmental systems framework. This perspective states that influences on reading achievement do not exist in isolation and that we must direct attention towards examining the interactions between the different layers of the systems (psychological and contextual factors) and the learners? developmental outcomes (reading comprehension achievement). The reading comprehension is measured based on two reading purposes; a) reading for literary experience, b) reading to acquire and use information. Data of 7805 grade 4 students participating in PIRLS 2016 (Progress in International Reading Literacy Study) is investigated. A multilevel linear regression analysis is used to model the relationship between parents? SES, early literacy experience and reading comprehension achievement. These home-based factors explain 15% of variance in reading achievement. Early literacy activities before school and parents? educational level, particularly fathers? education have a substantial impact on reading comprehension achievement. These findings have important practical implications for encouraging early literacy experience before school and enhancing parents? educational involvement